Awareness of HIV/AIDS among the pregnant women and their husbands attending ANC clinic in a tertiary care centre in Chennai - Edward, Shanthi (International Journal Of Community Medicine And Public Health, 2017)
Background: In India the total number of people living with HIV (PLHIV) was estimated to be 2.1 million in 2015 and number of new cases estimated at 86,000. The prevalence of HIV among pregnant women in India is high and the awareness on HIV/AIDs is low among women in India .Awareness of HIV is important in antenatal mothers as they are vulnerable and encouraging early HIV testing will augment the PPTCT (Prevention of Parent to Child Transmission) services. Hence it is prime importance to create awareness among pregnant women to protect them from HIV infection. This study was conducted to find out the awareness level among pregnant women and their husbands as husbands play an important role in prevention of HIV in their spouses. Methods: A cross-sectional study was conducted at ANC clinic in Sri Ramachandra Medical College, Porur, Chennai. All antenatal women who visited the ANC clinic for the first time along with their husbands were selected as the subjects. Sample size was 200 (100 couples). After obtaining Informed Consent from the subjects, a semi structured questionnaire was administered. Data was collected and analysed using SPSS software version 21. Results: One hundred couples were included in the study. Seventy five percent of subjects did not accept that they are at risk and majority of them were husbands (79%) when compared to wives (71%). Above 75% of wives knew mother to child transmission whereas only 65% of husbands knew it. Willingness to undergo HIV test was more among wives (83%) than husbands (75%). Conclusions: A large effort to be taken to impart the information about the HIV/AIDS to husbands to change their attitude. At least one ANC visit by pregnant women should be made mandatory to have their husbands with them to sensitise them on HIV/AIDS.